Virus plaque assay: effective detection of virus plaque forming cells at the early stage of lymphocyte activation by mitogen and alloantigen. - Kasahara, T (1979)
Activated lymphocytes were detected quantitatively by virus plaque assay (VPA) during the course of lymphocyte cultures stimulated by mitogen or alloantigen. In Con A-stimulated cultures, the number of virus-plaque forming cells (V--PFC) was a more sensitive method of detecting the early stage of lymphocyte activation than [3H]-thymidine (3H-TdR) incorporation. This evidence was obtained by two methods of collecting cells of each stage. First, when Con A-activated lymphocytes were fractionated by velocity sedimentation at unit gravity to separate cell populations according to each cell stage, the ratio of the number of V-PFC to the radioactivity of incorporated [3H]-TdR was larger in the earlier stage of cell cycle than in the later stage. Second, when cultured lymphocytes were synchronized directly by addition of excess thymidine and colchicine, similar results were obtained. In primary mixed lymphocyte cultures, the generation of cytotoxic lymphocytes (CTL) was correlated better with the proliferative response than with V-PFC production. It was also found that both the incorporation of [3H]-TdR and the generation of CTL were abrogated by cytosine arabinoside (Ara-C) added to cultures up to one day before assay, whilst the generation of V-PFC was not so markedly affected by Ara-C. These findings suggest that V-PFC represent the number of precursor cells which require one or more generations to differentiate to CTL and not simply the number of effector lymphoyctes already exhibiting cytotoxicity.